Future of sensorimotor and psychomotor dysfunction in mental disorders: emerging tools, methodological challenges, and the road ahead - Hirjak, Dusan; Mittal, Vijay A.; Meyer-Lindenberg, Andreas; Northoff, Georg (The American journal of psychiatry, 2025)
PsychiatryOnline.org is the platform for all American Psychiatric Association Publishing journals, DSM, and bestselling textbooks, as well as APA Practice Guidelines, and continuing medical education.